INDEPENDENT WOMEN IN THE DIGITAL ARENA: NEGOTIATING IDENTITY AND POWER IN CONTEMPORARY ISLAMIC COMMUNICATION - Arkanuddin Padang; Kamalia Kamalia (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study examines how the identity of independent women is negotiated in Indonesia's digital sphere through the framework of Islamic communication. Integrating Judith Butler's gender performativity and Manuel Castells' network society, the research interrogates meaning production, resistance, and discourse circulation. Using qualitative methods-virtual ethnography, digital content documentation, and Krippendorff's content analysis-the study applies textual description, symbolic interpretation, and social explanation, with triangulation ensuring validity. Findings reveal three key configurations: support celebrating women's agency and financial independence; resistance reinforcing domestic roles and masculine hierarchies; and negotiation reconciling independence with sharia principles. Word cloud analysis highlights nodes such as “strong-independent-woman-love” and “man-family-relationship,” while sentiment analysis shows mostly positive responses, though qualitative reading uncovers intense frictions. Theoretically, the study affirms Butler's thesis of performativity and Castells' notion of the digital arena as a networked space of conflict. Contributions lie in demonstrating women's independence as a symbolic struggle over legitimacy, control, and power, with practical implications for inclusive religious dialogue, gender-sensitive policies, and digital literacy.